2019
DOI: 10.1183/23120541.00138-2019
|View full text |Cite
|
Sign up to set email alerts
|

miR-200 family members reduce senescence and restore idiopathic pulmonary fibrosis type II alveolar epithelial cell transdifferentiation

Abstract: RationaleAlveolar type II (ATII) cells act as adult stem cells contributing to alveolar type I (ATI) cell renewal and play a major role in idiopathic pulmonary fibrosis (IPF), as supported by familial cases harbouring mutations in genes specifically expressed by these cells. During IPF, ATII cells lose their regenerative potential and aberrantly express pathways contributing to epithelial–mesenchymal transition (EMT). The microRNA miR-200 family is downregulated in IPF, but its effect on human IPF ATII cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…The sum of this evidence supports the new interpretative key for IPF pathogenesis that has emerged in recent years: ATII stemness failure, as a consequence of the ATII-to-ATI trans-differentiation blockade, seems to be responsible for the hyperactivation of ATII cells and the upregulation of several upstream pathways that are major drivers of EMT, besides directly stimulating fibroblast proliferation and collagen secretion in a paracrine fashion [8].…”
Section: Editorialsupporting
confidence: 73%
“…The sum of this evidence supports the new interpretative key for IPF pathogenesis that has emerged in recent years: ATII stemness failure, as a consequence of the ATII-to-ATI trans-differentiation blockade, seems to be responsible for the hyperactivation of ATII cells and the upregulation of several upstream pathways that are major drivers of EMT, besides directly stimulating fibroblast proliferation and collagen secretion in a paracrine fashion [8].…”
Section: Editorialsupporting
confidence: 73%
“…Transfection of AECs with miR-200a and miR-141 reduces epithelial mesenchymal transition (EMT) and the expression of cellular senescence markers including p16 and p21, but does not improve AEC proliferation capacity. In contrast, transfection with miR-200b/c increases differentiation of senescent type II AECs into type I AECs, decreases EMT, and reduces disease severity in animal models of pulmonary fibrosis ( 142 145 ).…”
Section: Non-coding Rnas In Aging Ipf and Copdmentioning
confidence: 99%
“…miRNAs are short (∼22 nt) single-stranded ribonucleic acids functioning as post-transcriptional regulators of gene expression that play important roles by binding to specific sequences, blocking translation, or causing degradation of the target mRNA, which results in gene silencing. Through various mechanisms, some miRNAs (eg, miR-21, [ 55 , 56 ] miR-31, [ 57 ] miR-145, [ 58 ] miR-154, [ 59 ] and miR-199a [ 60 ] ) play a role in promoting fibrosis during the pathogenesis of IPF, and their expression levels are often elevated, while others (such as let-7d, [ 56 , 61 ] miR-9, [ 62 ] miR-18a, [ 63 ] miR-26a, [ 56 ] miR-27b, [ 64 ] miR-29, [ 65 ] miR-30a, [ 56 , 66 ] miR-155, [ 67 ] miR-200, [ 68 ] miR-221, [ 69 ] miR-323a, [ 70 ] miR-326, [ 71 ] miR-338, [ 72 ] miR-375, [ 73 ] and miR-486 [ 74 ] ) prevent fibrosis, and their expression levels are reduced. One recent study demonstrated that the long-intervening non-coding RNAs (lincRNAs) LINC00960 and LINC01140 can regulate fibroblast proliferation and inflammation, while changes in LINC01140 expression may mediate a reduced inflammatory response in IPF fibroblasts.…”
Section: Etiology: Environmental Genetic and Epigenetic Factorsmentioning
confidence: 99%